Cooperative supramolecular polymerization of a perylene diimide derivative and its impact on electron-transporting properties. Issue 46 (16th November 2017) - Basak, Dipankar; Pal, Deep Sankar; Sakurai, Tsuneaki; Yoneda, Satoru; Seki, Shu; Ghosh, Suhrit
Abstract : H-bonding-promoted supramolecular polymerization of a perylene diimide (PDI) building block and its impact on charge carrier mobility. Abstract : H-bonding-promoted supramolecular polymerization of a perylene diimide (PDI) building block and its impact on charge carrier mobility were studied.PDI-1, containing a carboxylic acid group, exhibits H-aggregation in a non-polar solvent decalin while in THF or chloroform it remains in the monomeric form. In contrast, the control moleculePDI-2, containing an ester group does not show aggregation even in decalin, indicating that H-bonding among the carboxylic acid is primarily responsible for H-aggregation, which is further verified by the FT-IR study. A variable temperature UV/Vis study establishes a cooperative pathway for the supramolecular polymerization ofPDI-1 . Microscopy images show a short fibrillar morphology. Flash-photolysis time-resolved microwave conductivity (FP-TRMC) measurements reveal significantly higher electrical conductivity for thePDI-1 film prepared from decalin compared with that prepared from THF/MeOH or the film of non-aggregatedPDI-2 prepared from decalin. By combining the transient absorption spectroscopy data (that estimate the charge carrier generation efficiency) and the TRMC evaluated conductivity, the 1D charge carrier mobility ofPDI-1 ( μ e, 1D ) is estimated to be 0.24 cm 2 V −1 s −1, which is among the top values reported for any PDI derivative measured using the same technique.